Sectoral productivity and spillover effects of FDI in Latin America - Gabriele Tondl; Jorge A. Fornero (FIW - Research Centre International Economics, 2010)
Empirical studies analysing productivity effects of inward FDI in Latin America (LA) are inconclusive. We argue that investigating aggregate FDI masks interesting effects of FDI that take place within and across sectors. Moreover, the potential of FDI to generate productivity effects differs across sectors. For these reasons and because sectoral FDI intensities vary significantly among LA countries and change over time, we investigate the productivity effects of FDI in eight different sectors including the primary sector, manufacturing and services. Besides FDI, sector-specific institutional factors, education and a sectors export share are considered as control variables. Given the likely endogeneity of variables, a GMM system estimation approach is used. The results indicate that positive productivity effects can be found in all sectors, although they may depend on specific conditions or are limited to a certain time period. Direct productivity effects are highest in the primary sector (agriculture, mining and petroleum production) and in financial services. In contrast, FDI in manufacturing and in transport and telecommunications generates productivity spillovers to nearly all other sectors.
Keywords: F39; O4; C32; C33; 330; FDI; productivity; sector level; Latin America